Nano Moth-eye Structures Fabricated Using Ultra-thin Photoresist and Combined Dry and Wet Etches - Sood, Rachit; Tu, Chaoran; Bamford, Douglas; Henseley, Joel; Woolf, David; Menyuk, Curtis; Singh, Narsingh; Choa, Fow-Sen (SciTechnol, 2023)
Anti-Reflective (AR) coatings are used to suppress reflection and enhance optical transmission, but many coatings cannot withstand harsh environmental conditions. In this work, we report the fabrication of nanostructures on Gallium Arsenide (GaAs) via contact photolithography for anti-reflection applications in the mid-infrared (mid-IR) range. An E- beam mask was used to lithographically transfer nano-structure patterns to a SiO₂ etching mask and then further transfer the structure to gallium arsenide wafers. With a thin layer Photo Resist (PR) along with a combination of Reactive Ion Etching (RIE) and wet Buffered Oxide Etching (BOE), we were able to transfer the nanostructure patterns from the thin PR to the thick SiO₂ etching mask and then onto a wafer. The fabricated structures are squares and hexagons of feature size 900 nm, 1000 nm, 1100 nm, and the gap between two neighboring shapes is 400 nm. By varying the pitch of the structures, we observe improvement in the transmission over the mid-IR range (500-2000 cm⁻¹ wavenumber). Experimental results of coated and uncoated GaAs are obtained using the Fourier Transform Infrared Spectroscopy (FTIR) while theoretical results of coated GaAs are shown using the Rigorous Coupled Wave Analysis (RCWA). This work provides a better success rate and a more readily available mass production technique to fabricate the sub-wavelength nanostructures. The theoretical results obtained using RCWA agree well with experimental results to show the overall 69% transmission with a one-side coated gallium arsenide wafer.
Keywords: Anti-reflection; Moth eye structures; Mid-IR; fabrication; Photolithography; Wet etching; Newton rings